IMPLICATIONS OF XENOPHOBIC ATTACKS ON NIGERIANS AND NIGERIA-SOUTH AFRICA DIPLOMATIC RELATIONS: A REVIEW OF RE-CURRENT ISSUES - ABDULRASHEED ABDULYAKEEN; MUHAMMAD RABIU (International Studies Journal)
This study identifies factors that influence the rise in Xenophobia attacks in South Africa and how that affect diplomatic relations between Nigeria and South Africa on the global stage. Using frustration-aggression theory as its theoretical framework. Using secondary sources of data collection in our quest to adequately reflect the issues involved in this study, interdisciplinary approach to historical research was adopted using content analysis. Finding of this study revealed that massive evacuation of foreign businesses from South Africa have increase the level of poverty and unemployment in South Africa. It also found that competition over jobs and government housing is perhaps the most frequently cited explanation for South African xenophobia, the evidence is mixed. This study conclude that Nigeria and South Africa diplomatic ties has been negatively affected by the xenophobic attacks. The consequential effect cut across economic, political and socio-cultural diplomatic relations between both countries. The study offers some practical steps to tackle the menace which include: South African government should enhance her diplomatic relations with Nigeria and other African countries whose citizens have fall victims of xenophobic attacks in their countries, a pragmatic measures should be taken to eradicate discrimination in South Africa.